Pursuing Graduate Study: Factors Underlying Undergraduate Engineering Students' Decisions. Issue 1 (5th February 2018) - Borrego, Maura; Knight, David B.; Gibbs, Kenneth; Crede, Erin
Abstract: Background: Enrollment of US students in engineering graduate programs is declining, the proportion of underrepresented groups being even lower at the graduate level than it is at undergraduate levels. Purpose: The purpose of this study is to explore engineering undergraduate student perceptions about graduate study, how these perceptions impact their decisions to pursue graduate study, and whether or how these differ by sex and race/ethnicity. Design/Method: We administered a survey about graduate study to 1082 undergraduate engineering students from four US institutions. Student characteristics included sex, race/ethnicity, and year in college. Exploratory Factor Analysis identified factors related to Social Cognitive Career Theory (SCCT). We created multinomial logistic regression models to predict intention to pursue a master's or PhD degree. Results: Identified factors were Self‐efficacy, Outcome expectations, Supports, Barriers, and Choice actions. Model fit statistics indicate a strong model. Only Choice actions was not significant. Few sex and race/ethnicity differences held once factors were added to the models. Hispanic students were more than twice as likely to indicate they were planning on enrolling in a master's program relative to no graduate school. Conclusions: Self‐efficacy most strongly influenced graduate school intention. For every one‐unit increase in students' self‐efficacy, they were over 8 times more likely to plan to enroll in a master's program and 13 times more likely to enroll in a PhD program, relative to not attending graduate school. Implications for research and practice are discussed.